Lavender essential oil on postmenopausal women with insomnia: Double-blind randomized trial. (June 2021) - dos Reis Lucena, Leandro; dos Santos-Junior, Jair Guilherme; Tufik, Sergio; Hachul, Helena
Graphical abstract: Highlights: The effect of aromatherapy in postmenopausal women with insomnia was assessed. We found a tendency of improvement in wake after sleep onset (WASO) between groups. The intervention group presented 42.2 min less than control group in WASO. The intervention group showed enhanced sleep efficiency and menopausal symptoms. Overall, both groups presented increased sleep quality after intervention. Abstract: Background: To evaluate the effect of Lavandula angustifolia essential oil inhalation on sleep and menopausal symptoms in postmenopausal women with insomnia. Participants: 35 postmenopausal women with a clinical diagnosis of insomnia were included, 17 in Aroma Group (AG) and 18 in Placebo Group (PG). Methods: In this double-blind, randomized controlled trial, PG participants inhaled sunflower oil and AG participants inhaled Lavandula angustifolia essential oil, for 29 days. Both groups received sleep hygiene guidelines before the intervention and weekly follow-up during it. Evaluations were performed before and after intervention. All statistical analyses and intention-to-treat test were performed in SPSS 22. Sleep quality (Primary outcome) was measured by Pittsburgh Sleep Quality Index. Secondary outcomes were polysomnography data, severity of insomnia, anxiety and depression symptoms, and postmenopausal symptoms. Results: There were no significant differences between groups after intervention in the primary outcome ( P = 0.22; effect size=0.69); however, a tendency of improvement in wake after sleep onset (WASO) was observed ( P = 0.07; effect size=0.81; B = 42.2). Both groups presented better sleep quality over time (AG P < 0.001; PG P = 0.011). AG participants showed a significant decrease in sleep onset latency ( P = 0.001), depression levels ( P = 0.025), hot flashes ( P < 0.001), postmenopausal symptoms ( P < 0.001) and, in polysomnography data, increased sleep efficiency ( P = 0.002) compared to baseline. Conclusion: Although no significant differences were observed between groups, our data presented a tendency of improvement in WASO. Moreover, AG participants had enhanced overall sleep pattern, quality and sleep efficiency. Weekly follow-up and sleep hygiene instructions were essential for both groups to show improvement in almost all outcomes. Clinical trial registration: Brazilian Registry of Clinical Trials, www.ensaiosclinicos.gov.br, RBR-5q5t5z.